Tata Ruang Pura Pedaleman Giri Kendeng Desa Klinting Kecamatan Somagede di Kabupaten Banyumas - Nopidha Ardyansah (UM Purwokerto Press, 2022)
In Klinting village, Somagede district, Banyumas regency, people who practice the faith of Hindu religion consists of about 6,9% of the village population. Before taking in the Hindu religion, they were practicing a Kejawen branch faith called Wayah Kaki. They practice their faith in Pura Pedaleman Giri Kendeng which is also located at Klinting village. After some development, today Pura Pedaleman Giri Kendeng has become the center of activity for people who practice the Hindu religion in Banyumas. The spatial design which consists of: spatial elements, spatial organizations, circulation, orientation, and the hierarchy of space from this temple located in Banyumas regency, Central Java, become the basis for the curiosity of the researchers to discover it. For that, the research methodology used is the qualitative method, with observation and documentation as the data collection technique. The research results are: 1) Pura Pedaleman Giri Kendeng apply the concept of Tri Mandala and the concept of Desa Kala Patra in its spatial plan, 2) Spatial element of the temple comprised of: Candi Bentar, Balai Wantilan, Kori Agung, Aling-Aling, Balai Piyasan, Panglurah, Padmasana, Candi Gedung, and Taman Sari, 3) The orientation of the temple is facing to the east, 4) The highest hierarchy is the building in Utama Mandala area.